Phase I Trial of Triapine–Cisplatin–Paclitaxel Chemotherapy for Advanced Stage or Metastatic Solid Tumor Cancers - Kunos, Charles A.; Chu, Edward; Makower, Della; Kaubisch, Andreas; Sznol, Mario; Ivy, Susan Percy (Frontiers in Oncology, 2017)
Ribonucleotide reductase (RNR) is an enzyme involved in the de novo synthesis of deoxyribonucleotides, which are critical for DNA replication and DNA repair. Triapine is a small-molecule RNR inhibitor. A phase I trial studied the safety of triapine in combination with cisplatin-paclitaxel in patients with advanced stage or metastatic solid tumor cancers in an effort to capitalize on disrupted DNA damage repair. A total of 13 patients with a variety of previously-treated cancers were given a 96-hour continuous intravenous (i.v.) infusion of triapine (40-120 mg/m2) on day 1, and then 3-hour i.v. paclitaxel (80 mg/m2) followed by 1-hour i.v. cisplatin (50-75 mg/m2) on day 3. This combination regimen was repeated every 21 days. The maximum tolerated dose (MTD) for each agent was identified to be triapine (80 mg/m2), cisplatin (50 mg/m2), and paclitaxel (80 mg/m2). Common grade 3 or 4 toxicities included reversible anemia, leukopenia, thrombocytopenia, or electrolyte abnormalities. The combination regimen of triapine-cisplatin-paclitaxel resulted in no objective responses; however, five (83%) of six patients treated at the MTD had stable disease between one and eight months duration. This phase I study showed that the combination regimen of triapine-cisplatin-paclitaxel was safe, and provides a rational basis for a follow-up phase II trial to evaluate efficacy and progression-free survival in women with metastatic or recurrent uterine cervix cancer.